Root Submergence by Decoronation and Root-End Resection of a Maxillary Incisor with Concrescence: A Case Report - Keith R. Boyer; James Ywom (Taylor & Francis Group, 2023)
ABSTRACTBackground Concrescence (cemental fusion) of roots poses difficulties for surgical and endodontic treatment. Decoronation is a procedure typically used for root banking of ankylosed teeth to preserve alveolar ridge width and height.Case Description This article presents a case in which root submergence was accomplished on an unrestorable and infected maxillary central incisor by decoronation and root-end surgery. This was performed to preserve a fused lateral incisor for its use as a fixed partial denture abutment to achieve a functional and esthetic result. Cone-beam computed tomography aided in the diagnosis, surgical planning, and follow-up for this case.